Preparation for Test in Russian as a Foreign Language through Extracurricular Activities (Proceedings of Southern Federal University. Philology, 2018)
Kholisakhon E. Ismailova, Olga V. Bondareva (Moscow, Russian Federation)The article is devoted to problem of organization of extracurricular work of students of the preparatory faculty aiming at forming their oral communication skills and cultural competence in learning in the language environment. The main attention is paid to the formation of students’ listening skills. Attention to this problem is due to the need to improve the effectiveness of students learning Russian as a foreign language for a more successful completion of their final test. Search for various ways to enhance learning has led to the necessity of using opportunities of extracurricular work forms as an additional means of teaching Russian as a foreign language.Key words: Russian as a foreign language, extracurricular activities, intercultural communication, teaching dialogical speech, testing on the Russian language.